Impaired Fibrous Repair: A Possible Contributor to Atherosclerotic Plaque Vulnerability in Patients With Type II Diabetes - Edsfeldt, Andreas; Gonçalves, Isabel; Grufman, Helena; Nitulescu, Mihaela; Dunér, Pontus; Bengtsson, Eva; Mollet, Inês G.; Persson, Ana; Nilsson, Marie; Orho-Melander, Marju; Melander, Olle; Björkbacka, Harry; et al. (Arteriosclerosis, thrombosis, and vascular biology, 2014)
OBJECTIVE—Diabetes mellitus (DM) type II is increasing rapidly worldwide. Patients with DM II have a greater atherosclerotic burden and higher risk of developing cardiovascular complications. Inflammation has been proposed as the main cause for the high risk of atherosclerotic disease in DM II. In this study, we compared markers of inflammation and fibrous repair in plaques from subjects with and without DM II. APPROACH AND RESULTS—Carotid endarterectomy specimens were obtained from 63 patients with and 131 without DM. Plaque structure, connective tissue proteins, inflammatory cells, and markers were analyzed by immunohistochemistry, ELISA, Mesoscale, and Luminex technology. Carotid plaques from diabetics had lower levels of extracellular matrix proteins, elastin, and collagen, which are critical for plaque stability. Plaques from diabetics had reduced levels of platelet-derived growth factor and matrix metalloproteinase-2, both important for tissue repair. No differences were observed in inflammatory markers in plaques from diabetic and nondiabetic patients. CONCLUSION—This study suggests that atherosclerotic plaques in subjects with DM II are more prone to rupture because of impaired repair responses rather than to increased vascular inflammation. Although this study did not have a mechanistic design, our findings suggest that targeting impaired repair responses in carotid plaques may help to increase our understanding of atherosclerotic plaque development and vulnerability in patients with DM II.